2019
DOI: 10.4067/s0718-381x2019000400385
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the First Archwires Placement on the Everyday Activities of Orthodontics Patients

Abstract: Orthodontic treatment (OT) is essential for the aesthetic and functional rehabilitation of the chewing apparatus, however it may lead to certain complications which can have a negative impact on patients' everyday lives. The study included patients of the Dental Teaching Clinic of Universidad de La Frontera who were undergoing OT for the first time, with the placement of their first orthodontic arch. To analyse the impact of the placement of the first arches on everyday activities (EDA), patients completed a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…5 Pain is chiefly caused by the movement of the teeth and may impair the patient's quality of life, cause uneasiness, and interfere with everyday activities such as mastication and speech. 6 In 2002, a study by Kluemper et al suggested that pain is a major reason for discontinuing the treatment. 7 Most of the patients undergoing fixed appliance treatment complain about pain, discomfort, oral ulceration, tongue soreness, and functional limitations (BERGIUS et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…5 Pain is chiefly caused by the movement of the teeth and may impair the patient's quality of life, cause uneasiness, and interfere with everyday activities such as mastication and speech. 6 In 2002, a study by Kluemper et al suggested that pain is a major reason for discontinuing the treatment. 7 Most of the patients undergoing fixed appliance treatment complain about pain, discomfort, oral ulceration, tongue soreness, and functional limitations (BERGIUS et al, 2000).…”
Section: Introductionmentioning
confidence: 99%